“Efecto de cinco dosis de humus de la lombriz en el cultivo de repollo (brassica oleracea L.) var. Corazón de buey, en la zona del alto Huallag-Tocache” - Gonzales Pérez, Marlon Roberto (2015)
The present research aimed to evaluate and determine the effect of different doses of vermicompost on the performance and profitability of the crop of cabbage (Brassica oleracea l.) variety Ox Heart abte to Alto Huallaga - Tocache. The research was conducted on the grounds of Fundo "Caríbbean" owned by Mariela Hemandez Escudero, with cadastral code No. 108327, in the village of Santo Cristo, located by the altemate road to the town of Uchiza understanding of the district and province Tocache, San Martín Region. Statistical Design randomized complete block (RCBD) with tour blocks and six treatments, with a total of 24 experimental units were used. The information gathered in the field was processed with SPSS Statistical Program 19, which uses the P-value comparison significant differences in confidence levets of O.OS and 0.01 in the analysis of variance (ANOVA) and multiple range test of Duncan P s O.OS. The doses used were: T1 (6000 kg ha-1 of vermicompost, T2 (7000 kg ha-1 of vermicompost, T3 8000 kg ha-1 ofvermicompost, T4 (9000 kg.ha-1 of vermicompost and TS (10000 kg ha-1 of vermicompost, TO (control without application) the variables evaluated were: plant height (cm), number of leaves per plant, diameter of the head (cm) Weight head (g), yield (kg ha-1 ) and economic analysis. the results indicate that the dose of 10 t ha-1 of vermicompost was treatment (TS) which determinad the greatest effect on performance with 20406.25 kh.ha-1 and the benefiVcost of 0.81 and a net profit of S/. 11,830.57 soles, respectively. Keywords: Assess, identify, effect, dose, treatments, humus, worm, variety, crop yield, cabbage, Heart of Ox.